Becoming a Global Village: The History of Globalization in Bali - Fransiska Dewi Setiowati Sunaryo; I Ketut Ardhana (Paramita: Historical Studies Journal, 2025)
Abstract: Bali, currently known as one of the world's tourist destinations, has long historical roots. However, Bali is slowly experiencing changes, namely on the one hand trying to adopt and adapt various existing changes, but on the other hand trying to maintain these customs and traditions so that their cultural roots are not eroded. The purpose of this article is to analyze what continues and what changes occur as a result of external influences. The research method used is a qualitative method with a historical approach, expected to provide a better understanding of how Bali, which was once closed to outside cultures, is now seen as an open fortress. Document sources and in-depth interviews were used to dig up information about the history of globalization in Bali. The conclusion in this research reveals that the arrival of Dutch colonial influence, which initiated the development of tourism in Bali during the colonial period, impacted customs and traditions on the one hand. On the other hand, Balinese people began to recognize various artistic influences and art-making techniques as they were introduced later. Ubud and Kuta in Bali have turned into a global village, which on the one hand is very strong with traditional roots, but is very adaptive to Western influences. Abstrak: Bali yang saat ini dikenal sebagai salah satu destinasi wisata dunia memiliki akar sejarah yang panjang. Namun demikian, Bali secara perlahan mengalami perubahan, yaitu di satu sisi berusaha mengadopsi dan mengadaptasi berbagai perubahan yang ada, namun di sisi lain berusaha mempertahankan adat dan tradisi tersebut agar akar budayanya tidak terkikis. Tujuan dari artikel ini adalah untuk menganalisis apa saja yang tetap dipertahankan dan perubahan apa saja yang terjadi akibat pengaruh dari luar. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan historis yang diharapkan dapat memberikan pemahaman yang lebih baik tentang bagaimana Bali yang dulunya tertutup terhadap budaya luar, kini dipandang sebagai benteng yang terbuka. Sumber-sumber dokumen serta wawancara mendalam digunakan untuk menggali informasi mengenai sejarah globalisasi di Bali. Kesimpulan dalam penelitian ini mengungkapkan bahwa kedatangan pengaruh kolonial Belanda yang mengawali perkembangan pariwisata di Bali pada masa kolonial berdampak pada adat istiadat di satu sisi, dan di sisi lain, masyarakat Bali mulai mengenal berbagai pengaruh artistik dan teknik pembuatan karya seni yang diperkenalkan kemudian. Ubud dan Kuta di Bali telah berubah menjadi sebuah desa global yang di satu sisi sangat kental dengan akar tradisi namun sangat adaptif terhadap pengaruh Barat.